Implementation of the Equality and Non-Discrimination Standard in the Current Precedents Issued by the Ecuadorian Constitutional Court - María Luisa Azanza Torres (Universidad Hemisferios, 2022)
This paper intends to show, the current state of the principle of equality and non-discrimination in the current precedents issued by the Ecuadorian Constitutional Court. For this purpose, we analyze the rulings on this matter by the Ecuadorian Constitutional Court since 2008 when the new Constitution was released. There are several articles throughout the current Constitution regarding equality and non-discrimination, and they are wide and open for interpretation. This has motivated different approaches by the judges that have not been able to reach to a uniform decision-making argument in the first rules about this matter. This study provides evidence of the evolution of precedents concerning concepts such as suspect categories and levels of scrutiny in the context of equality and non-discrimination standard. We also have compared this standard test with precedents issued by other foreign and international Courts. Based on this analysis, we have determinated the current equality and non-discrimination standard and its scope and limitations.